2015
DOI: 10.3390/fib3020151
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Scaffolds from Low Molecular Weight Poly(ester amide)s Based on Glycolic Acid, Adipic Acid and Odd or Even Diamines

Abstract: Electrospinning of regular poly(ester amide)s (PEAs) constituted by glycolic acid, adipic acid and diamines with five and six carbon atoms has been carried out. Selected PEAs were constituted by natural origin products and could be easily prepared by a polycondensation method that avoids tedious protection and deprotection steps usually required for obtaining polymers with a regular sequence. Nevertheless, the synthesis had some limitations that mainly concerned the final low/moderate molecular weight that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…39,40 In 2005, Vera et al reported inspiring work that poly(ester-amide)s containing glycolate were degradable in enzymatic media and hydrolytic conditions. [41][42][43][44] Since materials containing glycolate units typically exhibit low gas permeability, we anticipated that these degradable poly(ester-amide)s derived from glycolide would have both promising mechanical and gas barrier properties (Chart 1C).…”
Section: Introductionmentioning
confidence: 99%
“…39,40 In 2005, Vera et al reported inspiring work that poly(ester-amide)s containing glycolate were degradable in enzymatic media and hydrolytic conditions. [41][42][43][44] Since materials containing glycolate units typically exhibit low gas permeability, we anticipated that these degradable poly(ester-amide)s derived from glycolide would have both promising mechanical and gas barrier properties (Chart 1C).…”
Section: Introductionmentioning
confidence: 99%